Signal Detection Methods Based on Less Matrix Inversion for Massive MIMO Systems - Jiarui Ding (MATEC Web of Conferences, 2018)
In this paper, we will represent several methods that can reduce the computational complexity to detect signals for Uplink Massive MIMO Systems. Then we will show the simulation performance of these methods and analyse them. Finally we will give improvement for better performance.